Burden of coronary artery calcification in ANCA-associated vasculitis - Claire Cook; Brittany Weber; Catherine Ahola; Zachary S. Wallace; Michael Hendrickson; Anushri Parakh; Sandeep Hedgire; Michael Lu (RMD Open)
Background Cardiovascular disease (CVD) is a leading cause of death in ANCA-associated vasculitis (AAV). Screening and primary cardiovascular prevention may improve outcomes.Methods We identified patients in the 2002–2019 Mass General Brigham AAV cohort with thoracic CT scans obtained for other clinical purposes. Coronary artery calcium (CAC) scores and age, sex and race-standardised CAC percentiles were calculated. Quantile regression was used to identify differences by ANCA type, and Gray’s test examined differences in major adverse cardiac events by CAC score.Results Of 175 included patients, 127 (73%) were MPO-ANCA+and 48 (27%) were PR3-ANCA+. The median CAC score was 17 (IQR 0, 334) and CAC percentile was 45 (IQR 0, 78); 65 (39%) patients had CAC of ≥100. The total CAC score was higher in patients with MPO-ANCA+AAV vs PR3-ANCA+AAV (median 24 vs 1, p=0.003), as was the standardised CAC percentile (50th vs 34th, p=0.02). Of 116 (66%) patients with non-zero CAC scores, only 29 (25%) were on a statin. In a time-to-event analysis, CAC of 100 or higher trended towards association with higher risk of major adverse cardiovascular events (χ2=1.9, p=0.16).Conclusion A majority of patients with AAV had clinically significant CAC. There were differences in CAC burden among those with MPO-ANCA+AAV versus PR3-ANCA+AAV. Although CAC is associated with CVD risk and an indication for statins, the use was inconsistent. The role of CT imaging to screen for CVD and guide primary prevention in AAV requires further study.